Perception and orientation issues in human control of robot motion - Gray Cobb, Susan Valerie (1991)
The use of remote teach controls for programming industrial robots has led to concern over programmer safety and reliability. The primary issue is the close proximity to the robot arm required for the programmer or maintainer to clearly see the tool actions, and it is feared that errors in robot control could result in injury. The further concern that variations in teach control design could cause "negative transfer" of learning has led to a call for standardisation of robot teach controls. However,at present there is insufficient data to provide suitable design recommendations. This is because previous researchers have measured control performance on very general, and completely different, programming tasks.